Peran Pemeriksaan Rutin Penyakit Sindrom Metabolik dalam Upaya Mengurangi Risiko Kerapuhan dengan Pemeriksaan Frail pada Kelompok Usia Lanjut - Noer Saelan Tadjudin; Muhammad Kharis Mahdaviqa; Kresna Bambang Fajarivaldi; Edwin Destra (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Metabolic syndrome, encompassing hypertension, elevated blood glucose levels, high cholesterol, and increased waist circumference, is a significant risk factor for frailty in older adults. The FRAIL questionnaire is a screening tool that assesses five components of frailty, enabling early detection for appropriate intervention. This community service program was conducted using the PDCA (Plan-Do-Check-Act) method with 93 elderly participants. Health education and screening for metabolic syndrome and frailty were performed using the FRAIL questionnaire. Among the participants, 22.58% were categorized as